Imperfect Competition and Basing-Point Pricing: Evidence from the Softwood Plywood Industry - Gilligan, Thomas W. (American Economic Review, 1992)
The Federal Trade Commission's action to eliminate basing-point pricing in the soft plywood industry during the mid 1970s created a natural experiment: the author finds that the FTC's action had no effect on the delivered price of the base-site product (Douglas fir plywood) but decreased the delivered price of the non-base-site product (pine plywood) for many consumers. The evidence suggests that the detrimental effects of basing-point pricing for economic welfare were reflected entirely in the behavior of non-base-site firms. Copyright 1992 by American Economic Association.